(3GdaUhd GdeNJGQI ef cJH CHj YKeGf YeQh Hf HMQ GdLGMXs - (3MeRI Hf GdMSf GdCUagGfj, CHhGdaQL,J (B360 (3g` s
(3ChdgG (B:s
(3GYde Gfj hEjGc eJi JMGcefG Edi cQec bVi dj Ydjc, heJi GQJaYfG Edi Ybdc s
(3BNQgG (B:s
(3HFSJ GdUfGYI GdNWGHI, Ef bqUQ oNUe, hEf CZQb CKe s
(3GfXQgG eY GdLRA GdChd Qbe (B636 (3COHs
(3HGdeYgO fSNI GNJjGQ YHOGddg Hf MSGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B277 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B78 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B336s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B96 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs